Evaluation of readability of Turkish websites on substance addiction - Çifci, Hatice Kübra; Kozanhan, Betül; Solak, İbrahim (Journal of Dependence, 2020)
Objective: The aim of this study was to examine the readability level of Turkish websites containing information about substance addiction (SA) according to the Atesman and Bezirci-Yılmaz readability formulas and to evaluate the content of these websites. Method: A search was performed in November 2019 by typing the word "substance addiction" in Google’s search engine (https://www.google.com). We evaluated the websites on the first 15 pages of Google’s search engine results. Commercial websites, advertisement websites, chat websites, forum websites, magazine websites, websites containing only images or videos, and websites with less than 10 sentences were excluded from the study. The average number of syllables, average number of words with 4 or more syllables, and Atesman and Bezirci-Yilmaz readability values were calculated. Results: The average number of syllables and average number of words with 4 or more syllables were respectively 2.90±0.10 and 4.31±1.37. The mean Atesman and Bezirci-Yilmaz readability values were respectively 46.03±11.67 and 14.04±4.12. Conclusion: The readability level of Turkish websites containing information about SA was "difficult" according to the Atesman readability formula and at "undergraduate level" according to the Bezirci-Yılmaz readability formula.